Clinico - epidemiological study of corrosive poisoning by different agents in Dhaka Medical College Hospital (Bangladesh Medical Journal, 2014)
Acute poisoning is a serious threat to society and one of the commonest causes of mortality and morbidity. The purpose of this study was to have an idea about the pattern of corrosive poisoning and their socio-demographic background. This study was conducted in Dhaka Medical College Hospital over a period of six months from January to June, 2008. The total respondents were 126 in number. All patients, aged 13 years and above with acute corrosive poisoning were included. The results revealed that 23% were male and 77% female. Male, female ratio was 1: 3.34. Age between (13-30) years (88.09%) was the most vulnerable. Most of the patients (45.25%) had a background of secondary education. Students (43.7%) were the dominant group followed by housewives (30.2%). Most of the patients (80.2%) came from urban area. 88.9% attempted to commit suicide. Familial disharmony (75.4%) was the leading motive of poisoning. Twenty five types of corrosive agents were identified; out of which 83.34% cases took either Savlon (51.59%) or Harpic (31.75%). Female is the most vulnerable target who attempted to commit suicide. DOI: http://dx.doi.org/10.3329/bmj.v42i3.19000 Bangladesh Med J. 2013 Sept; 42 (3): 78-81